Reassessing Restorative Justice: Addressing Sexual Violence Cases in Indonesi - Wibowo, Ribut Hari; Busro, Ahmad; Purwanti, Ani (Indonesia Law Review, 2023)
This study examines”Restorative”Justice in the settlement of sexual violence crimes. The research method used in this study is normative juridical, using a statute approach. The aim of this research is to determine the effectiveness of Restorative Justice in resolving the problems of cases of sexual violence that have occurred in Indonesia. The results of this study include that Restorative Justice is not effectively applied to cases of sexual violence because it cannot fulfill”the principles of respect for human”dignity, nondiscrimination, the best interests of the victim, justice, benefit and legal certainty for the victim as stipulated in the Law, Constitution Number 12 of 2022 concerning Crimes of Sexual Violence and the fulfillment of victims' rights.